Siskopatuh as a Government Public Relations Strategy - Past Novel Larasaty; Riska Afriyanti (Jurnal Komunikasi Global, 2020)
Following various issues regarding malpractices and frauds done by irresponsible Umrah and Hajj Organiser Companies (PPIU) in Indonesia, the Indonesian Ministry of Religious Affairs (Kemenag), is assigned with a more significant challenge to overcome the problem that causes billion rupiah loss on the side of the customer (jamaah). One of the efforts tried to be implemented is by creating Integrated Computerised Management for Umrah and Special Hajj, also known as SISKOPATUH as the channel to register, monitor and control the flow of Umrah and Hajj application and process for both jamaah and PPIU. This research drew attention on how Kemenag has tried to socialise and implement SISKOPATUH that they have planned to be the protector of jamaah.  In-depth interviews were done with stakeholders of Umrah and Hajj organisers; two from government and three from private sectors. The findings reveal that a number of strategies were used by Kemenag to communicate their programme to protect the people from Umrah and Hajj malpractices. Setelah beberapa isu dan kasus penipuan jamaah oleh Perusahaan Penyelenggara Ibadah Umrah (PPIU) dalam beberapa tahun belakangan, pemerintah Indonesia, Kementerian Agama Republik Indonesia (Kemenag) mendapat tantangan besar untuk menangani kasus yang merugikan jamaah hinga miliaran rupiah. Salah satu upaya yang dilakukan adalah dengan menciptakan sebuah sistem aplikasi SISKOPATUH sebagai kanal untuk mendaftarkan, mengawasi dan mengontrol alur proses pemberangkatan jamaah Umrah dan Haji, yang digunakan oleh jamaah dan PPIU. Penelitian ini berfokus pada upaya Kemenag dalam menyosialisasikan dan menjalankan kebijakan SISKOPATUH kepada publik dan PPIU. Wawancara mendalam dilakukan kepada dua orang pihak Kemenag dan 3 orang pihak swasta. Hasil penelitian memperlihatkan bahwa Kemenag menjalankan sejumlah strategi untuk menyampaikan program pemerintah dalam rangka melindungi jamaah dari penipuan dan penyalahgunaan penyelenggaraan ibadah Haji dan Umrah.